Towards ballistic transport CVD graphene by controlled removal of polymer residues. (3rd December 2022) - Duan, Tianbo; Li, Hu; Papadakis, Raffaello; Leifer, Klaus
Abstract: Polymer-assisted wet transfer of chemical vapor deposited (CVD) graphene has achieved great success towards the true potential for large-scale electronic applications, while the lack of an efficient polymer removal method has been regarded as a crucial factor for realizing high carrier mobility in graphene devices. Hereby, we report an efficient and facile method to clean polymer residues on graphene surface by merely employing solvent mixture of isopropanol (IPA) and water (H2 O). Raman spectroscopy shows an intact crystal structure of graphene after treatment, and the x-ray photoelectron spectroscopy indicates a significant decrease in the C–O and C=O bond signals, which is mainly attributed to the removal of polymer residues and further confirmed by subsequent atomic force microscopy analysis. More importantly, our gated measurements demonstrate that the proposed approach has resulted in a 3-fold increase of the carrier mobility in CVD graphene with the electron mobility close to 10 000 cm 2 V −1 S −1, corresponding to an electron mean free path beyond 100 nm. This intrigues the promising application for this novel method in achieving ballistic transport for CVD graphene devices.